EU Member States' Voting for Authorizing Genetically Engineered Crops: a Regulatory Gridlock - Richard D. Smart; Matthias Blum; Justus Wesseler (German Journal of Agricultural Economics (GJAE), 2015)
Several authors suggest a gridlock of the European Union's (EU's) approval process for genetically engineered (GE) crops. We analyse the voting behaviour of EU Member States (MSs) for voting results from 2003 to 2015 on the approval of GE crops to test for a gridlock; no reliable data are available pre-2003 - a time which included the EU's moratorium on GE crops. After the European Food Safety Authority (EFSA) has given a favourable opinion on the safety of a GE crop, the Standing Committee on the Food Chain and Animal Health (SCFCAH) votes on the application. If the SCFCAH reaches no decision, the Appeal Committee (AC) (pre the Treaty of Lisbon: the Council) votes on the application; if no decision is reached here, the final decision is left to the European Commission. All EU Member States (MSs) are represented on both committees; decisions are made by a qualified majority (QM) voting system, the rules of which have changed over time. Our data include 50 events; and 61 ballots at the SCFCAH and 57 ballots at the Council / AC. A QM has been achieved once only at the SCFCAH, but never at Council. At Council / AC level, Austria and Croatia have consistently voted against an approval, while The Netherlands has always supported approvals. All other MSs showed differences in their voting decisions at the SCFCAH and Council / AC level at least once. MS-fixed-effects are the major factors explaining the voting results supporting the gridlock hypothesis, while crop characteristics and crop use play no apparent role in MSs' voting behaviour. We maintain that a QM is unlikely following the latest directive for MSs to 'opt-out' on GE crop cultivation in their territories.
Keywords: 330